Traditional African vegetables’ seed access and management practices: case of Vernonia amygdalina (Delile) in southern Benin - Houegban, Jordan; Aglinglo, Lys Amavi; N’Danikou, Sognigbé; Tchokponhoué, Dèdéou A.; Amissah, Jacqueline Naalamle; Ankamah-Yeboah, Theresa; Achigan-Dako, Enoch (Frontiers in Sustainable Food Systems, 2024)
Vernonia amygdalina is an African traditional leafy vegetable which is a source of income for many households involved in its production in West and Central Africa. The species possesses several medicinal and nutritional properties. Despite its importance, there is limited information on farmers' access to seed, seed production practices, seed trade, and related constraints. This research aimed at investigating farmers' seed access and management practices. A non-probabilistic snowball method was used to sample and interview 164 bitter leaf seed sector actors from urban and peri-urban areas in Benin. Results indicated that vegetable farming is mainly practiced by men and it was the main occupation for 94.47% of the farmers interviewed. A significant association was found between the location and farmers' experience (p-value = 0.01358). A diversity of Vernonia amygdalina morphotypes were found. Sixty-three percent of the farmers surveyed use seeds as planting material, 29% use purchased seedlings and only 7% use stem cuttings for Vernonia amygdalina production.Most of the seeds used (74%) were from farmer-saved seeds, harvested from isolated plants during production. The main constraints to V. amygdalina production reported by farmers were the unavailability of seeds (41% of respondents), low germination percentage (18%) and low seed longevity (12%). Findings from this study can inform solutions to improve farmers' access to highquality seeds and enhance V. amygdalina vegetable production.